Sintesis Nanokomposit TiO2-Grafit untuk Degradasi Asap Rokok - Anggini, Aulia; Muldarisnur, Mulda (Jurnal Fisika Unand, 2021)
TiO2 nanoparticles and TiO2 – Graphite nanocomposite has been successfully synthesized by a simple heating method in a polymer solution. The particles formed were applied to measure the degradation time of harmful compounds in cigarette smoke using visible light. The polymer used was PEG 6000. The synthesis was carried out at a temperature of 600 °C with a holding time of 0 hour, 0.5 hours, and 1 hour. The results of XRD and UV Vis DRS characterization showed that the crystal size formed was 26.5 nm, and the bandgap energy was 2.98 eV, 2.95 eV, 3.07 eV, and 3.9 eV for TiO2 without holding time, TiO2 – G with a hold time of 0 hours, 0.5 hours, and 1 hour. The increase in holding time resulted in more stable crystals and had a higher degree of crystallinity. TiO2 – G nanocomposite can degrade cigarette smoke faster than TiO2 without graphite because the addition of graphite increasesthe light absorption ability of TiO2 in the visible light region. This matter shows that TiO2 – G nanocomposites are more efficient in degrading cigarette smoke than TiO2 nanoparticles without graphite.